A randomized trial of relationship education using Within Our Reach for economically vulnerable couples. Issue 3 (11th May 2022) - Barden, Sejal M.; Carlson, Ryan G.; Dillman Taylor, Dalena; Dickenson, Tammiee; Gao, Ruiqin
Abstract: Couples relationship education is grounded in teaching couples' skills and strategies to form and sustain healthy relationships. The purpose of this investigation was to examine the impact of a relationship education intervention on emotion regulation, individual distress, dyadic coping, and relationship adjustment utilizing a randomized control trial for economically vulnerable couples. The analysis sample included 1418 couples (2836 individuals) who were randomly assigned to receive the 12‐h Within Our Reach curriculum immediately, or to a wait‐list control group. We estimated multilevel growth curve models over time among outcomes between treatment and wait‐list control conditions. Treatment group couples demonstrated statistically significant improvements over the 6‐month study period on emotional regulation and dyadic coping when compared to their wait‐list group counterparts. Although models showed improvements in individual distress and relationship adjustments, these improvements did not amount to statistically significant group differences. Implications and limitations are also noted. 摘要: 夫妻关系教育的基础是教授夫妻形成和维持健康关系的技能和策略。本研究的调查目的是利用一项针对经济弱势夫妇的随机控制试验，研究关系教育干预对情绪调节、个人痛苦、双方应对和关系调整的影响。分析样本包括1, 418对夫妇（2, 836人），他们被随机分配到立即接受12小时的 "力所能及 " 项目课程，或进入等待名单的对照组。我们预估了一段时间内的多层次增长曲线模型，主要基于治疗和等待控制条件之间的结果情况的。在6个月的研究期间，治疗组的夫妇与等待名单组的夫妇相比，在情绪调节和双方处理关系方面有明显的改善。尽管模型显示在个人痛苦和关系调整方面有所改善，但这些改善并不等同于统计学上显著的群体差异。本文还指出了本研究的启示和局限性。